Food and nutrition education as a strategy to reduce food wastage in public elementary schools - Talita Balansin Rigon; Larissa Valério Cordeiro; Julicristie Machado Oliveira; Caroline Dario Capitani (Demetra, 2022)
Introduction: Food and nutrition education (FNE) activities in the context of school meals have been highlighted for contributing, among other possibilities, to the reduction in food wastage. Objective: To assess the impact of FNE activities aimed at reducing wastage in school meals. Methods: The study began with a diagnosis food wastage in two public elementary schools in Santa Bárbara do Oeste-SP and Limeira-SP, through monitoring of leftovers and food waste, for 12 non-consecutive days, at different times, between August and December 2019. After the diagnosis, the FNE activities were planned, prepared, and executed, with subsequent analysis of the results. The activities were carried out with elementary school classes (n=152 schoolchildren), allocated to “control” (n=77) and “intervention” (n=75) groups, to enable evaluation of the effectiveness of the FNE in reducing food wastage at the end of the study (control vs. intervention). Results: In both schools, the consumption of rice, beans, and the protein dish stood out, compared to the other preparations. Waste reduction was observed in both schools, in the intervention and control groups, when comparing the data before and during the intervention (p<0.05). The reductions in wastage in the intervention group were 62.0% in the SBO school and 43.1% in the Limeira school. Conclusion: FNE activities were effective, but long-term follow-up is recommended to assess their effectiveness.